The Effect of Up and Down Stairs and Uphill Training Methods on Increasing Sprint Running Speed - Ciko Firdaus (Journal of Physical Education and Sport Science, 2023)
ABSTRACT This study aims to determine the effect of up and down stairs and uphill training methods in increasing students' sprint running speed. This study uses an experimental method with an experimental class and a control class. The population of this research is 45 students of SMP Bustanul Falah Bandungsari. The sample was determined as many as 33 students including 14 students of class VIII as the experimental class and 19 students of class IX as the control class. The sampling technique used is simple random sampling, by taking samples from members of the population that are carried out randomly without paying attention to the strata in the population. The instrument used is the sprint assessment format. Data analysis using t test and F test. Based on the results of the research and discussion that has been obtained, it can be concluded that there is an effect of up and down stairs and uphill exercises on increasing students' sprint running speed, it is proven that the results of the calculation of the value of tcount 4.464 > ttable value 1.782 and Fcount 19.931 > Ftable 4.75. Then from the results of the pretest value has a mean of 7.43 and the posttest has an average value of 5.96. There is an increase by a difference of 1.47 seconds. The results showed that the application of the up and down stairs and uphill training methods gave a very good influence in increasing the sprint speed of class VIII students of SMP Bustanul Falah Bandungsari.